Computed Tomography Assessment of Linear Splenic Dimensions and their Correlation with Anthropometric Measurements in Nepalese Population - Crystal KC; Bikash Bikram Adhikari; Rakshya Parajuli (Journal of Nobel Medical College, 2023)
Background: Geographical locations and ethnicity may influence variations in normal spleen dimensions, potentially leading to errors in assessment. This study aimed to correlate splenic dimensions with anthropometry and predict their variation with age and body surface area.